Campur Kode dalam Komunikasi Santri di Pondok Pesantren Al-Hikmah Sukoharjo - Ferdian Achsani; Hilmi Mahya Masyhuda (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
The purpose of the research is to describe code mixing or billingualisme in communication among students of Al Hikmah Sukoharjo Islamic Boarding School. Daily conversation among students was analyzed as data of the research. This is descriptive qualitative study which use participant observation technique. technique of analysis was used by the researcher before, during, and after research in the field. This technique emphasize several stages namely data collection, data reduction, display data and conclusion. Data collection was obtained in two weeks then classified into sub category then drawn conclusion. The findings showed that some code mixings were used by students frequently were Javannese, Indonesia and arabic. The findings showed that billingualism wudu consists of 1) word insertion, 2) phrases insertion, 3) clauses insertion, and 4) idiom insertion.The main factor in using billingualism in communication among students is multicultural, education level of speaker and purpose of speech. Keywords: Code mixing, billingualism and communication